Production and purification of pDNA as a biopharmaceutical with application in oncolog - Pires, Carolina Freitas (2023)
This work reports the development of an upstream and downstream process to recover a model plasmid DNA (pDNA) with potential application in gene therapy, particularly targeting breast cancer. After the pDNA production, aqueous biphasic systems (ABS) were investigated to as a recovery and purification technique. The ABS composed of the tetrabutylphospnium bromide ([P4444]Br) ionic liquid (IL) and potassium citrate salt (C5H6K3O7·H2O) was identified as the most promising system promoting the isolation of pDNA with high purity. The partitioning behaviour of pDNA and ribonucleic acid (RNA) showed that for low concentrations of salt and IL, both classes of nucleic acids exhibit a tendency to be preferentially partitioned toward the bottom phase, mainly enriched in potassium citrate salt. However, and by properly engineering the concentration of both phase-forming components, at the mixture point composed of 25 wt% of [P4444]Br and 25 wt% of K3C6H5O7, pDNA was selectively recovered in the salt-rich phase with high purity. It was observed that pDNA is mostly recovered in its supercoiled isoform, and that the content of total proteins was reduced by 13% in comparison with the bacterial lysate sample. Also, purified pDNA exhibited the ability to confer resistance to Escherichia coli cells after heat-shock transformation, further supporting that it is purified with high integrity and functionality. Overall, a promising IL-based ABS technology for the purification of pDNA from bacterial lysates was developed in this work, in which the presence of IL seems to be responsible for upgrading the pDNA purity over some conventional systems. Envisaging the production of pDNA for gene therapy, future work should comprise the evaluation of the biological activity of purified pDNA and the assessment of endotoxin levels.